El Excentrico, 1965-12-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
December 5, 1965 [5 de diciembre de 1965] Ano 16, No 4. Cover has a photograph of American citizens protesting. The headline reads, "Mexican-Americans Picket E.O.C."